Exosomes derived from human amniotic epithelial cells accelerate diabetic wound healing via PI3K-AKT-mTOR-mediated promotion in angiogenesis and fibroblast function. Issue 1 (7th September 2020) - Wei, Pei; Zhong, Chenjian; Yang, Xiaolan; Shu, Futing; Xiao, Shichu; Gong, Teng; Luo, Pengfei; Li, Li; Chen, Zhaohong; Zheng, Yongjun; Xia, Zhaofan
Abstract: Background: Diabetic wounds are one of the most common and serious complications of diabetes mellitus, characterized by the dysfunction of wound-healing-related cells in quantity and quality. Our previous studies revealed that human amniotic epithelial cells (hAECs) could promote diabetic wound healing by paracrine action. Interestingly, numerous studies demonstrated that exosomes derived from stem cells are the critical paracrine vehicles for stem cell therapy. However, whether exosomes derived from hAECs (hAECs-Exos) mediate the effects of hAECs on diabetic wound healing remains unclear. This study aimed to investigate the biological effects of hAECs-Exos on diabetic wound healing and preliminarily elucidate the underlying mechanism. Methods: hAECs-Exos were isolated by ultracentrifugation and identified by transmission electron microscopy, dynamic light scattering and flow cytometry. A series of in vitro functional analyses were performed to assess the regulatory effects of hAECs-Exos on human fibroblasts (HFBs) and human umbilical vein endothelial cells (HUVECs) in a high-glycemic microenvironment. High-throughput sequencing and bioinformatics analyses were conducted to speculate the related mechanisms of actions of hAECs-Exos on HFBs and HUVECs. Subsequently, the role of the candidate signaling pathway of hAECs-Exos in regulating the function of HUVECs and HFBs, as well as in diabetic wound healing, was assessed. Results: hAECs-Exos presented a cup- or sphere-shaped morphology with a mean diameter of 105.89 ± 10.36 nm, were positive for CD63 and TSG101 and could be internalized by HFBs and HUVECs. After that, hAECs-Exos not only significantly promoted the proliferation and migration of HFBs, but also facilitated the angiogenic activity of HUVECs in vitro . High-throughput sequencing revealed enriched miRNAs of hAECs-Exos involved in wound healing. Kyoto Encyclopedia of Genes and Genomes and Gene Ontology analyses have shown that the target genes of the top 15 miRNAs were highly enriched in the PI3K-AKT pathway. Further functional studies demonstrated that the PI3K-AKT-mTOR pathway was necessary for the induced biological effects of hAECs-Exos on HFBs and HUVECs, as well as on wound healing, in diabetic mice. Conclusions: Our findings demonstrated that hAECs-Exos represent a promising, novel strategy for diabetic wound healing by promoting angiogenesis and fibroblast function via activation of the PI3K-AKT-mTOR pathway.